2018
DOI: 10.1088/1361-665x/aaad9c
|View full text |Cite
|
Sign up to set email alerts
|

A New Low-frequency Sonophoresis System Combined with Ultrasonic Motor and Transducer

Abstract: Low frequency sonophoresis (LFS) is currently being attempted as a transdermal drug delivery method in clinical areas. However, it lacks both an effective control method and the equipment to satisfy the varying drug dosage requirements of individual patients. Herein, a novel method aimed at controlling permeability is proposed and developed, using a pressure control strategy which is based on an accurate, adjustable and non-invasive ultrasound transdermal drug delivery system in in vitro LFS. The system mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Additionally, the duty ratio of the square waveform for MUN was investigated as previous studies have indicated that it has a significant impact on the performance of ultrasonic systems. 39,41,42 Therefore, we evaluated the influence of duty ratio on the signal intensities and signal-to-noise ratios of REEs with a wide range from 20% to 80%. To compare it at a constant nebulization rate of 30 μL min −1 , the voltage of MUN was adjusted accordingly (Table S-4†).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the duty ratio of the square waveform for MUN was investigated as previous studies have indicated that it has a significant impact on the performance of ultrasonic systems. 39,41,42 Therefore, we evaluated the influence of duty ratio on the signal intensities and signal-to-noise ratios of REEs with a wide range from 20% to 80%. To compare it at a constant nebulization rate of 30 μL min −1 , the voltage of MUN was adjusted accordingly (Table S-4†).…”
Section: Resultsmentioning
confidence: 99%
“…A new sonophoresis system of transdermal drug delivery, which involves the combination of an ultrasonic transducer and a linear ultrasonic motor, is designed to control permeability in in vitro LFS (Low frequency sonophoresis) [278] Surgical Instrument with Torque Assist…”
Section: Medical Endoscopementioning
confidence: 99%
“…(a) (b) Many surgical devices have high requirements for precision and response speeds. Ultrasonic motors have been gradually applied to surgical devices due to their high precision and quick response speeds [59][60][61][62][63][64][65], as shown in Fig. 8.…”
Section: Aerospace Engineeringmentioning
confidence: 99%